Glycemic Index of Sweet Corn and the Characteristics of their Flakes by Adding the Red Bean - Evan Daniels; Nur Wulandari; Didah Nur Faridah (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2023)
Consuming foods with a low glycemic index, such as sweet corn (Zea mays Saccharata), which has a high fiber content, can help lower the risk of diabetes. According to previous research, sweet corn is predicted to have a low glycemic index (GI). The study's goals were to determine the value of the glycemic index of corn and to produce low glycemic index instant flake products made from sweet corn and red beans. The glycemic index value of sweet corn was determined using a glycemic index test technique based on ISO 26642:2010E. The flakes was made with the addition of red beans reported to have the lowest glycemic index among legume, i.e. 26 in order to enhance the crude protein content of the flakes. Flakes were made in two formulas based on the proportion of red beans to sweet corn, namely formula 1 (30:70) and formula 2 (70:30). Proximate analysis was done according to AOAC 2005, total dietary fiber analysis according to AOAC Official Methods 985.29, and total starch analysis according to AOAC 2002.02. Texture analysis of the flakes was carried out using a texture analyzer and color analysis using a chromameter. The sweet corn was found to have a low GI (<55) i.e. 36. Formula 1 flakes contained more fat (db), carbohydrate (db), and total starch (db); while formula 2 flakes had more moisture, protein (db), and resistant starch (db). The resulting flakes have crispy texture (hardness of 553±5.09 gf for formula 1 and 519.05±6.86 gf for formula 2) and have yellow color (both are included in the yellow chromatic area).